Stres Kerja pada Perawat di Instalasi Rawat Inap RSU Darmayu Ponorogo - Muhammad Yazid Labib; Ani Asriani Basri; Eka Rosanti; Rindang Diannita (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Nurses have different levels of occupational stress. This research is to analyze the factors associated with the incidence of occupational stress on nurses in the inpatient installation at Darmayu Public Hospital. This type of research is cross-sectional. The population is 90 nurses with a sample of 73 nurses, the sample is taken by simple random sampling. The datas are collected by measuring stress using a stress diagnosis survey questionnaire from The Ministry of Manpower of Indonesia No. 5 2018 and NASA TLX questionnaire to assess workload. The statistical test used is Chi-Square. Based on the results of the Chi-Square test, it is found that there are no factors related to the incidence of occupational stress, both from the factors of gender (p = 0.836), working period (p = 0.572), nutritional status (p = 0.108), and workload (p = 0.434). From the results of this study it can be concluded that the average workload and work stress of nurses is moderate. Then there is no significant relationship between gender, working period, nutritional status, and workload with the incidence of occupational stress on nurses in the inpatient installation at Darmayu Ponorogo Hospital.